Deliberative Politics : Essays on Democracy and Disagreement. - Macedo, Stephen (Practical and Professional Ethics., 1999)
The banner of deliberative democracy is attracting increasing numbers of supporters, in both the world's older and newer democracies. This effort to renew democratic politics is widely seen as a reaction to the dominance of liberal constitutionalism. But many questions surround this new project. What does deliberative democracy stand for? What difference would deliberative practices make in the real world of political conflict and public policy design? What is the relationship between deliberative politics and liberal constitutional arrangements?